STUDIO DAN GALERI SENI ULM BANJARBARU - Wulandari, Lusi; Anhar, Pakhri (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The ULM Banjarbaru Studio and Art Gallery is a forum for developing interests and talents which functions to accommodate all artistic activities within the ULM Banjarbaru campus, including the process of creating and displaying works. This is motivated by the unavailability of a special, integrated place to support the activities of students engaged in the arts. This Studio and Art Gallery also goes hand in hand with efforts to increase the competency of educational practices by the Ministry of Education, Culture, Research and Technology as well as UUD NO. 12 of 2012. The concept of